Peran Struktur Sosial dalam Pembangunan Sarana Prasarana Permukiman Perkotaan (Studi Kasus: PLPBK Kelurahan Karangwaru Kecamatan Tegalrejo Kota Yogyakarta) - Yanuar Kusuma Wardani; Yori Herwangi; Ahmad Sarwadi (Jurnal Ilmu Pemerintahan Widya Praja, 2018)
Social structure is one of the important elements in development. Elements in the social structure will form relationships and form joint actions on the program. PLPBK Program in Karangwaru Village, Tegalrejo Sub-District, Yogyakarta City has focus on society. Social life is closely related to social structure. Based on the explanation, the purpose of this research is to determine the role of social structure in the PLPBK program in Karangwaru Village. The approach of this research is deductive qualitative. The method of analysis used is descriptive qualitative. Methods of data collection using field observation, secondary survey, and primary survey. Sampling technique of primary survey using non-probability sampling that is purposive sampling. The results showed that the social structure in Karangwaru Village has a positive and negative role in the PLPBK program. Social institutions, social groups, power and authority, and culture have a positive role while social stratification and social dynamics have a positive and negative role. The function of social structures such as maintaining patterns, integration, achieving objectives, and adaptation has been demonstrated by the social structure in the PLPBK program at Karangwaru Village.Keywords: Development; Infrastructure; Social Structure; Society